Comparative Study of the Photocatalytic Activity of Semiconductor Nanostructures and Their Hybrid Metal Nanocomposites on the Photodegradation of Malathion. (20th June 2011) - Fouad, Dina Mamdouh; Mohamed, Mona Bakr
Abstract : This work is devoted to synthesize different semiconductor nanoparticles and their metal-hybrid nanocomposites such as TiO2, Au/TiO2, ZnO, and Au/ZnO. The morphology and crystal structure of the prepared nanomaterials are characterized by the TEM and XRD, respectively. These materials are used as catalysts for the photodegradation of Malathion which is one of the most commonly used pesticides in the developing countries. The degradation of 10 ppm Malathion under ultraviolet (UV) and visible light in the presence of the different synthesized nanocomposites was analyzed with high-performance liquid chromatography (HPLC) and UV-Visible Spectra. A comprehensive study is carried out for the catalytic efficiency of the prepared nanoparticles. Different factors influencing the catalytic photodegradation are investigated, as different light source, surface coverage, and nature of the organic contaminants. The results indicate that hybrid nanocomposite of the semiconductor-metal hybrid serves as a better catalytic system compared with semiconductor nanoparticles themselves.